2013
DOI: 10.1149/05330.0049ecst
|View full text |Cite
|
Sign up to set email alerts
|

NaxCoO2 Cathode Material: Synthesized by Inverse Micro- Emulsion Method for Sodium Ion Batteries

Abstract: NaxCoO2 cathode material is synthesized by using inverse micro-emulsion method. The synthesized material has been characterized by using TG/DTA, XRD, SEM, and XPS, charge/discharge, cyclic voltammetry and EIS studies. XRD patterns reveal that the P2 phase formation of NaxCoO2. Electrochemical experiments have been performed by using CR-2032 type coin cells in which Na foil (Reference Electrode) and 1M NaClO4 in 1:1 PC/ EC (V/V) as an electrolyte. The synthesized NaxCoO2 material delivered the first cycle highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…The material exhibited ~120 mAh/g capacity analogous at 0.5 V Na in a limit of 3.75 V [122]. Later, B. Venkata Rami Reddy Jr. and Sukumaran Gopukumar reported a new kind of cathode material through the micro emulsion method, which exhibited the first cycle's ~162 mAh/g discharge capacity when cycled between 2.0 -4.2 V potential window, at a 0.1 C rate [123]. In 2014, Barpandaet al developed a competent family of compounds suitable for Na ions insertion and synthesized pyrophosphate compound having formulae Na 2-x (Fe 1-y Mn y )P 2 O 7 where 0 y 1 from the solid-state reaction method [124].…”
Section: Early Research (2012-2017)mentioning
confidence: 98%
See 1 more Smart Citation
“…The material exhibited ~120 mAh/g capacity analogous at 0.5 V Na in a limit of 3.75 V [122]. Later, B. Venkata Rami Reddy Jr. and Sukumaran Gopukumar reported a new kind of cathode material through the micro emulsion method, which exhibited the first cycle's ~162 mAh/g discharge capacity when cycled between 2.0 -4.2 V potential window, at a 0.1 C rate [123]. In 2014, Barpandaet al developed a competent family of compounds suitable for Na ions insertion and synthesized pyrophosphate compound having formulae Na 2-x (Fe 1-y Mn y )P 2 O 7 where 0 y 1 from the solid-state reaction method [124].…”
Section: Early Research (2012-2017)mentioning
confidence: 98%
“…The material exhibited ∼120 mAh/g capacity analogous at 0.5 V Na in a limit of 3.75 V [ 122 ]. Later, B. Venkata Rami Reddy Jr. and Sukumaran Gopukumar reported a new kind of cathode material through the micro emulsion method, which exhibited the first cycle's ∼162 mAh/g discharge capacity when cycled between 2.0 - 4.2 V potential window, at a 0.1 C rate [ 123 ]. In 2014, Barpanda et al.…”
Section: Contributions From Indian Researchersmentioning
confidence: 99%
“…The materials degrade rapidly, and one of the challenges preventing further development is the limited understanding of the intercalation-induced degradation mechanisms. A typical positive electrode comprises nanoparticles of the active material, carbon black for improved electron conductivity, and polymer binders for mechanical stabilization, all commonly added during cathode slurry formation . Recent research successfully revealed some of the internal mechanisms occurring in the active material during intercalation, yet the multicomponent nanoparticulate morphology makes it inherently challenging to study fundamental mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…A typical positive electrode comprises nanoparticles of the active material, carbon black for improved electron conductivity, and polymer binders for mechanical stabilization, all commonly added during cathode slurry formation. 7 Recent research successfully revealed some of the internal mechanisms occurring in the active material during intercalation, yet the multicomponent nanoparticulate morphology makes it inherently challenging to study fundamental mechanisms. Much insight could arise from investigating single crystals, yet the intercalation dynamics and poor electric conductivity limit the crystal sizes that can be efficiently intercalated to the microscale.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Generally, NCO has been synthesized by using various methods viz., solid state method, hydrothermal followed by solid state method, etc. Our earlier report 28 deals with the synthesis of NCO using inverse microemulsion method and evaluating the electrochemical behaviour. Herein, we present our investigation on NCO, synthesized via sol-gel combustion technique using glycine 29 as a chelating agent as well as fuel which facilitates the uniform mixing, better yield and homogenous crystallite growth.…”
Section: Introductionmentioning
confidence: 99%